Feasibility and Field Performance of a Simultaneous Syphilis and HIV Point-of-Care Test Based Screening Strategy in at Risk Populations in Edmonton, Canada. (23rd January 2014) - Bergman, Joshua; Gratrix, Jennifer; Plitt, Sabrina; Fenton, Jayne; Archibald, Chris; Wong, Tom; Singh, Ameeta E.
Abstract : Few studies have evaluated the feasibility of delivering syphilis point-of-care (POC) testing in outreach (nonclinical) settings in resource rich countries. The objectives of the study were to evaluate the feasibility and diagnostic performance of performing both HIV and syphilis POC testing in outreach settings and to document new cases identified in the study population. 1, 265 outreach testing visits were offered syphilis and HIV POC testing and 81.5% (n = 1, 031 ) consented to testing. In our population, the SD Bioline 3.0 Syphilis Test had a sensitivity of 85.3% [CI (68.9–95.0)], specificity of 100.0% [CI (99.6–100.0)], positive predictive value (PPV) of 100.0% [CI (88.1–100.0)], and negative predictive value (NPV) of 99.5% [CI (98.9–99.8)]. Test characteristics for the INSTI HIV-1/HIV-2 Antibody Test had a 100.0% sensitivity [CI (39.8–100.00], 99.8 specificity [CI (99.3–100)], 66.7% PPV [CI (22.3–95.7)], and 100.0% NPV [CI (99.6–100.0)]. Four new cases of syphilis and four new HIV cases were diagnosed. In summary, at risk population seeking STI testing found POC tests to be acceptable, the POC tests performed well in outreach settings, and new cases of syphilis and HIV were identified and linked to treatment and care.